Сучасний стан вивчення фольклору та етнології в Японії - Катаока, Х. (Народна творчість та етнографія, 2007)
It is a common opinion that the national consciousness is being formed on the foundation of the union with the other members of your ethnic group as well as on the understanding of the differences between your ethnic group and others. Japanese national consciousness was born in the 18th–20th centuries as a reaction on the fear of the influence of the Western countries. In the ethnocentric theories (specifically “kokugaku”), it was mainly the study of ancient Japan and its culture. Due to the active policy of the Meiji’s government (1868–1912), the conception of national consciousness was spread among the entire population. In Japanese language, the word nation for the long period of time meant only Japanese nation and was confused with the wider term, which meant any ethnic group.